Pendidikan Islam Inklusif dalam Perspektif Maqasid Al-Syari’ah: Studi Lapangan Sekolah Dasar Islam Ramah Anak Berkebutuhan Khusus di Pekanbaru - Ruri Liana Anugrah; Dewi Sartika (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to examine in depth how the principles of Maqasid al-Shari'ah are implemented in the practice of inclusive Islamic education in Islamic Elementary Schools friendly to Children with Special Needs (ABK) in Pekanbaru City. This study uses a qualitative approach with a field study method. Data collection techniques are carried out through participatory observation, in-depth interviews with class teachers and ABK assistant teachers, school principals, and parents of students, as well as documentation of the school curriculum and programs. The total informants in this study were 12 people. The results of the study indicate that the values ​​of Maqasid al-Shari'ah are implemented in five concrete forms of protection: Hifzh al-Dīn (protecting religion), Hifzh al-Nafs (protecting the soul), Hifzh al-‘Aql (protecting reason), Hifzh al-Nasl (protecting offspring), and Hifzh al-Māl (protecting wealth). The inclusive Islamic education implemented in the school is not merely an administrative approach, but a real representation of the implementation of maqasid syar'i in modern education. This study recommends the integration of a maqasid-based education curriculum to strengthen aspects of justice, protection, and empowerment of children with special needs in Islamic school environments.